Defining Disability: Understandings of and Attitudes Towards Ableism and Disability - Friedman, Carli; Owen, Aleksa L. (Disability Studies Quarterly, 2017)
Disabled people, amidst political and social gains, continue to experience discrimination in multiple areas. Understanding how such discrimination, named here as ableism, operates is important and may require studying perspectives of people who do not claim a disability identity. Ableism may be expressed in a number of ways, and examining how a particular group, in this case siblings of disabled people, understand and value disability may contribute to overall understandings about how ableism works. Thus, the purpose of this study is to explore relationships between siblings of disabled people's broad societal understandings of disability and their attitudes towards it. In order to tease out this relationship further we have also examined factors that impact how people define disability. Using both social psychological and sociological approaches, we have contextualized individual attitudes as providing additional new information about social meanings of disability, and set this study's results against the larger backdrops of debates over meanings of disability within Disability Studies. In our research, participants revealed complex understandings of disability, but most often defined disability as preventing or slowing action, as an atypical function, a lack of independence, and as a socially constructed obstacle. Participants' unconscious (implicit) disability attitudes significantly related to their understandings of disability as lacking independence, impairment, and/or in relation to the norm, and their conscious (explicit) disability attitudes. Moreover, longer employment in a disability-related industry was correlated with defining disability as a general difference, rather than as slowing or limiting of tasks.